Conservation approaches on historic government buildings in Malaysia / Izatul Laili Jabar, Rohaslinda Ramele Ramli and Hasnizan Aksah - Jabar, Izatul Laili; Ramli, Rohaslinda Ramele; Aksah, Hasnizan (2012)
At present, all conservation and preservation programs in Malaysia are subject to various policies and guidelines; and evaluation of planning applications before the developers, owners and agencies involvement in the conservation works are advised. This study is aimed to investigate current conservation approaches on historic government buildings, focusing on the guidelines imposed, issues and problems in conservation projects at every stage from preliminary study and planning, dilapidation study, tender document preparation, building conservation works until the last stage of handover and management of building. Methods taken during the study are unstructured interviews with related professionals, and site investigation on each case study which represents three states; Kuala Lumpur, Malacca and Penang. Based on current conservation approach issued by the Department of -ational Heritage and Ministry of Information, Communication and Culture, the study also included related organizations such as Kuala Lumpur City Hall, Malacca Historic City Council, Penang Municipal Council, appointed contractors and conservators. Findings are expected to produce standardization on the conservation approach and guidelines for conservation works done on historic government buildings, solutions for issues and problems in the conservation projects, and a common understanding for every organization to work collaboratively towards better conservation practice.